A tutored discourse on microcontrollers, single board computers and their applications to monitor and control chemical reactions. Issue 2 (6th January 2020) - Fitzpatrick, Daniel E.; O'Brien, Matthew; Ley, Steven V.
Abstract : This Tutored Discourse constitutes a preliminary exposure on how synthesis chemists can engage positively with inexpensive, low-power microcontrollers to aid control, monitoring and optimisation of chemical reactions. Abstract : This Tutored Discourse constitutes a preliminary exposure on how synthesis chemists can engage positively with inexpensive, low-power microcontrollers to aid control, monitoring and optimisation of chemical reactions. The acquired skillset adds a new aspect to the toolbox of molecular construction, especially going forward in an ever-increasing digital machine-assisted world. It attempts to break down some of the barriers and myths to adoption of these techniques and to provide a basis for further innovation and discovery.